Researching sensitive topics for the police – insights from the UK. Issue 2 (11th June 2018) - Rogers, Colin
Abstract : Purpose: The purpose of this paper is to illustrate how practical research can be undertaken into sensitive issues within the criminal justice system having cognisance of the needs of those subject to the research process. Design/methodology/approach: A mixed methods design which was complicated due to the subject matter being explored, that of historical reporting of sexual offences. Confidential questionnaires and focus group method utilised, but in constant contact with specialised victim support service to ensure rights of victims understood and interwoven into the design. Findings: Even though there are some very sensitive areas within the criminal justice system where it is believed research is difficult to undertake, it can be achieved by constant reference to the needs of the victim and strict confidentiality. Given the right circumstances and approach, research into what has been previously considered areas of difficulty can be researched effectively. Research limitations/implications: Due to the research methods explored an utilised, a template for research methodology can be seen which can be transferred into any other sensitive topic that requires research. In addition, by undertaking this method, previously unheard voices of victims of historical crimes can be utilised to inform official policy and practice. However, a limitation of the approach can be the low number of respondents wishing to take part. Practical implications: Victims have an opportunity to influence public policy. The methods utilised "opens up" the possibility for replication of research into other sensitive areas of the CJS. The methods utilised involved a number of Criminal Justice Agencies which assisted in maximising their understanding of victims experiences thorough the partnership approach. The research methods and results influencing training methods of the police as first responders to such incidents. Social implications: The social implications of this paper are that it will encourage other researchers not to be afraid of what appears to be "hard to reach" and sensitive topics in terms of social science research. This will allow for greater numbers of marginalised individuals and victims to engage and influence the criminal justice system, thereby influencing public policy and improving the way victims of crime are treated. Originality/value: This paper is one of the few, if any, that explores ethical problems and sensitive topics such as historical reporting of sexual offences. It will have resonance for those who wish to undertake similar types of research.